The Role of Spousal Support in Reducing Parental Stress among Indonesian Dual-Earner Couples - Langerya Rizal, Gumi; Govindasamy, Priyalatha (Program Studi PGMI, 2025)
The purpose of this study is to examine the direct role of spousal support in reducing parental stress among dual-earner families in Indonesia using the Actor-Partner Interdependence Model (APIM). Rapid socioeconomic changes have increased parental responsibilities, especially in dual-earner families, heightening parental stress. Using a quantitative cross-sectional design, data were collected from 246 dual-earner couples. Parental Stress Scale and Spousal Support Scale were employed to measure parental stress and spousal support, respectively. Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis revealed significant actor effects: husband's support significantly decreased wife's parental stress (β = -0.356, p < 0.001), and wife's support significantly reduced husband's parental stress (β = -0.341, p < 0.001). These findings emphasize the critical role of spousal support in alleviating parental stress, highlighting its importance in enhancing family well-being. The study offers practical recommendations for interventions and policies aimed at strengthening spousal support to improve parenting experiences within dual-earner families.